EMPLOYEE BRANDING SEBAGAI STRATEGI KOMUNIKASI ORGANISASI UNTUK MENGKOMUNIKASIKAN CITRA MEREK (BRAND-IMAGE) - Yeni Rosilawati (Jurnal Ilmu Komunikasi, 2008)
Brand image can be projected through all aspects coming from the organization. From logo, location, store layout, product quality,service quality and also can be projected from the manner and attitude of the employees of organization toward their customers. That is called employee brabding. As Miles and Mangold said that employee branding is “the process by which employees internalized the desired brand image and are motivated to project the image to cus- tomers and other organizational consituents”. Employees can be strengthening and create brand image through their behavior and attitude. Employee brand-building behaviors may include courtesy, responsiveness, reliability, helpfulness, and empathy, among others. Such behaviors have been shown to contribute to consumers’ perceptions of service quality and may result in higher levels of customer retention and loyalty. The succesfullness of communication depend on how the organization projected their image to their publics. With employee branding, the employees help the organization by showing their empaht and exploring customers -cultural experiences. The real branding is creating brand by comprising all about the intangible aspects and tangible aspects.